New Steroidal Saponins and Sterol Glycosides from Paris polyphylla var. yunnanensis - Wu, Xia; Wang, Lei; Wang, Guo-Cai; Wang, Hui; Dai, Yi; Ye, Wen-Cai; Li, Yao-Lan (Planta Medica, 2012)
Four new steroidal saponins, pariposides A–D (1–4), and two new sterol glycosides, pariposides E–F (5-6), along with eight known steroidal saponins (7-14), two known sterol glycosides (15–16), and two known ecdysteroids (17–18), were isolated from the roots of Paris polyphylla var. yunnanensis. Among them, compounds 1–4 are the first spirostanol saponins with a peroxy group located between C-5 and C-8 of the aglycone. Their structures were determined by detailed spectroscopic analyses and chemical methods. All the isolated compounds were evaluated for their in vitro cytotoxicities against human nasopharyngeal carcinoma epithelial (CNE) cells, and steroidal saponins 7, 11, 13, and 14 showed a potent antiproliferative effect on CNE cells with IC50 values of 9.2, 4.7, 11.1, and 2.7 µM, respectively.
Keywords: Paris polyphylla var. yunnanensis; Liliaceae; steroidal saponin; sterol glycoside; cytotoxic activities